(untitled) (USA, 1999)
This volume presents the fundamentals of various agricultural tools and machines and describes the types most commonly used for various operations. The scope of crop production is defined rather broadly to include greenhouse production and forestry in addition to field crops.Important peripheral topics also are covered, such as transport machines, machine systems, and technology transfer.
Keywords: Agricultural Engineering,Plant production engineering,Kỹ thuật nông nghiệp